The contribution of copyright-based industries to the South African economy - Pouris, Anastassios; Inglesi-Lotz, Roula (South African Journal of Science, 2017)
We report the results of an effort to measure the contribution of copyright-based industries to the South African economy. Following the methodology of the World Intellectual Property Organization, we identify the copyright industry’s contribution to GDP, employment, imports and exports in South Africa for the period 1970–2009. It was estimated that the sector contributed 4.1% to GDP – more than the contributions of other sectors such as agriculture and food, beverages and tobacco. Because of this quantified importance of the copyright-based industries, we recommend that relevant South African policy authorities and policymakers should monitor and publicise regularly the performance of the copyright-based industries as well as promote programmes for their development and growth. Significance: • Copyright-based industries have the potential to play an important role in job creation and economic growth. • Our findings suggest that policymakers should design and promote the implementation of future policies and strategies related to these sectors.